Outcome of cluster endophthalmitis in western plain region of Nepal - Bajimaya, S; Kansakar, I; Sharma, BR; Byanju, R (Kathmandu University Medical Journal, 2010)
Background: Post-operative endophthalmitis remains one of the most visually devastating complications of cataract surgery. Cluster endophthalmitis is defined as five or more cases of endophthalmitis occurring on a particular day in a single operating room in one centre. Excessive inflammation, particularly in the early post-operative phase, should be regarded as infective endophthalmitis. Early diagnosis and immediate intervention in such case, lead to salvage of eye as well as better visual outcome. Objective: To find out the causative organisms and visual outcome after an outbreak of post-operative endophthalmitis in high volume cataract surgical centre. Materials and methods: Retrospective, interventional case series of 19 patients with acute post-operative endophthalmitis after manual small incision cataract surgery in a single day, underwent vitreous tap and received intravitreal Vancomycin, amikacin and Dexamethasone. Subconjunctival vancomycin was given at the end of the procedure. Vitreous samples were stained using Grams stain, Giemsa stain and KOH mount. Samples were sent to the hospital's microbiology laboratory for culture and sensitivity testing. All patients received intravenous ciprofloxacin for 3 days and oral ciprofloxacin for 7 days. Topical Prednisolone acetate, Ofloxacin, Gentamycin and atropine were given to all patients. Patients were followed up till 6 weeks. Results: 10 eyes had vitreous tap culture negative (52.6%) where as 9 eyes (47.4%) had bacterial culture growth. The culture reports showed 4 cases (21%) of Staphylococcus epidermidis, 3 cases (15.8%) of Staphylococcus aureus and 2 cases (10.5%) of mixed growth. 48 hours after the intervention, 15 patients improved clinically. On sixth week follow up, 7 eyes (37%) had visual acuity better than 6/18, 7 eyes had 6/18 to 6/60 and 5 eyes had visual acuity between 1/60 to 5/60. Conclusion: Intravitreal antibiotics and steroid, along with systemic ciprofloxacin and subconjunctival vancomycin has good visual outcome for post operative cluster endophthalmitis. Key words: Manual small incision cataract surgery; Cluster Endophthalmitis; Nepal DOI: 10.3126/kumj.v8i1.3232 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 102-108